Caracterización del sistema de manejo de asnos (Equus asinus) en la parroquia San Isidro, Sucre, Manabí - Chávez Figueroa, Kevin Damián (2025)
This study aimed to characterise the management systems of donkeys (Equus asinus) in San Isidro parish, Sucre canton, Manabí province, in order to identify current practices and key areas requiring improvement. A structured survey comprising 23 questions was administered to 150 owners using the Epicollect5 tool, and frequency analysis was performed on qualitative variables. The findings revealed that 72% of respondents use donkeys for agricultural activities, and 82% have kept them for over seven years, highlighting their importance as productive assets in rural areas. However, 57.33% of owners have not received any training in proper handling, and only 6% report having advanced knowledge, indicating a significant technical gap. In terms of nutrition, although 90.67% of the animals are fed on pasture and concentrates, just 15.33% receive regular nutritional supplements, adversely affecting their health and performance. Despite 98.67% having access to clean water, sanitary practices remain inadequate: 82% of owners do not vaccinate their animals, and 84.67% deworm them irregularly. The most commonly reported health issues were internal and external parasites (44.67%) and hoof problems (39.33%). Furthermore, 92% of owners do not incorporate technology in their management, and 86% are unaware of improved care practices. The infrastructure for donkey management is precarious, reflecting a low level of technological advancement in their care. Most animals remain in basic housing conditions. Moreover, there is a significant lack of knowledge about modern tools that could improve their welfare and handling.